Upaya Guru PAK dalam Meningkatkan Keaktifan dan Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Kristen di SMP Negeri 8 Palangka Raya - Novia Crista Febrianti (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study examines the efforts of Christian Religious Education teachers to enhance students' learning activities and motivation in Christian Religious Education classes at SMP Negeri 8 Palangka Raya. The research was motivated by the presence of students who demonstrated low participation and limited learning motivation, creating challenges for teachers in developing effective instructional strategies. A qualitative descriptive approach was employed using purposive sampling. The primary informant was the Christian Religious Education teacher, while the school principal and several students served as supporting informants. Data were collected through observation, interviews, and documentation and analyzed using the interactive model of Miles and Huberman, including data condensation, data display, and conclusion drawing. The findings indicate that students' learning activities and motivation were generally satisfactory, although several students remained less active and less motivated. Teachers addressed these issues by applying varied teaching methods, creating a conducive learning environment, providing motivation and reinforcement, utilizing engaging learning media, and implementing contextual learning. The success of these efforts was supported by adequate educational facilities, strong school support, positive teacher–student relationships, and family involvement. However, several obstacles persisted, including low student interest and self-confidence, differences in learning abilities, excessive social media use, limited instructional time, and insufficient family support. The study concludes that varied, student-centered instructional strategies play an important role in increasing learning activities and motivation while supporting more meaningful Christian Religious Education learning.